Potentials of blockchain technology in supply chain management: Long-term judgments of an international expert panel - Kopyto, Matthias; Lechler, Sabrina; von der Gracht, Heiko A.; Hartmann, Evi (Technological Forecasting and Social Change, 2020)
Blockchain technology offers numerous fields of application, especially for supply chain management (SCM), as it could supersede the middleman activities in many transaction-based processes along the supply chain. Blockchain technology has a disruptive impact on supply chain design and operations, making the exploration of future application scenarios of great importance. However, knowledge in this field remains scarce, despite the subject's strategical value. This empirical study addresses this gap by conducting an interdisciplinary Delphi survey. Long-term judgments from an international panel of 108 designated experts from academia, industry, and politics/associations with different context-related backgrounds (blockchain, SCM, hybrid functions) were systematically analyzed. The results reveal prospective scenarios how blockchains will be applied in SCM by 2035 and which SCM-specific obstacles need to be solved in advance. One key finding reveals that even though blockchain technology is said to enable transactions between untrusted parties, trust-related advantages of blockchain technology are not directly transferable to SCM without additional conditions. Counterintuitively, active trust management between supply chain partners will still be needed. Nonetheless, this research reveals that blockchain technology will be strongly applied in SCM by 2035 and thus provides beneficial orientation and stimulating perspectives for decision-makers in the field.<br
Keywords: Blockchain; Future; Technology; Supply Chain; Expert judgments; Delphi study